SEMIOTICS OF LYRIC AND MEANING OF MOTIVATION FROM NCT DREAM WITH TITLE “LIFE IS STILL GOING ON” - Almasah Tsabitah (MEDIALOG: Jurnal Ilmu Komunikasi, 2021)
NCT Dream is a boyband from South Korea that has succeeded in gaining success in the international arena. NCT Dream embraces teenage children who have lost their enthusiasm for life. NCT Dream gives encouragement to teenagers through their songs. more This research entitled Semiotics Analysis of the meaning of Motivation Song Lyrics “Life is Still Going On” Work NCT Dream. This research is intended to find out the meaning contained in the lyrics of this song and it examined how the signifiers and signified. The theory used and relevant is the Ferdinand De Saussure Theory. The method in this study uses qualitative methods. The results of this research were found that the lyrics of the NCT Dream song Life Is Still Going On contains a meaning of a motivational message. In addition, this research is able to provide the meaning of the parable which is described through Ferdinand De Saussures’ semiotic analysis theory